ปัจจัยที่เกี่ยวข้องกับความสามารถในการสร้างสรรค์ของพยาบาลในโรงพยาบาลมหาวิทยาลัย - สุชาดา พาณิชกระจ่าง (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
Nurses’ creativity is a factor influencing quality of nursing care services. Identifying factors related to nurses’ creativity will help nurse administrators to be able to manage nursing organization more effectively. The purposes of this descriptive correlational research study were to examine the level of creativity and to identify factors related to creativity among nurses in university hospitals. The study sample comprised of 368 nurses working in university hospitals located in the northern region of Thailand. The research instruments consisted of: 1) Perception of Nurse Creativity Questionnaire, developed based on Guilford’s concept (1967) and reviewed literature by Suchada Phanitkrachang, Bunpitcha Chitpakdee, and Petsunee Thungjaroenkul and, 2) Factors Related to Nurses’ Creativity Questionnaire developed based on reviewed literature by Phanitkrachang, Chitpakdee, and Thungjaroenkul. Data were analyzed by using a computer package program. Statistics used for analysis were organized based on frequency, percentage, mean, standard deviation, and Spearman’s rank-order correlation coefficient.